Nutritive evaluation of some browse plant species collected from Algerian arid rangelands by chemical analyses and in vitro gas production - Bouazza L.; Boufennara S.; López S.; Bousseboua H.; Bodas R. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The objective was to evaluate the nutritive value of various Algerian browse and shrub species (Atriplex halimus, Artemisia campestris, Artemisia herba-alba, Astragalus gombiformis, Calobota saharae, Retama raetam, Stipagrostis pungens, Lygeum spartum and Stipa tenacissima). Chemical composition, and in vitro gas production kinetics for assessment of tannins using buffered rumen fluid were determined. Volume of gas (G) produced was recorded at several incubation times 3, 6, 9, 12, 16, 21, 26, 31, 36, 48, 72, 96, 120 and 144 h after inoculation time. France model G = A(1-e-c(t-L)) was used to estimate the fermentation kinetics parameters. In general, protein content in dicotyledon species was always greater than in monocotyledon grasses, these showing higher NDF and ADF and lower lignin contents than dicots. The values of degradation coefficient (ED) are between 0.623 g/g DM for A. campestris and 0.126 g/g DM for S. tenacissima. After 144 hours of incubation time, the highest cumulative gas production was observed for S. pungens (269 ml/g DM) and the lowest was obtained by A. halimus (185 ml/g DM). The lowest in vitro digestibilities were observed in monocotyledons (being particularly low for S. tenacissima), whereas dicots had significantly higher values. The CP was not correlated to gas production at all kinetic points. Chemical composition (NDF and CP), in vitro digestibility were the main influential variables determining the ranking. In conclusion, A. halimus, A. campestris, A. herba-alba and A. gombiformis can be considered of high nutritional value.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)